Graphical User Interface Design for Collaborative Virtual Environments - Mohd Kamal, Othman (IEEE, 2009)
The project aims to study, evaluate, analysis a collaborative virtual environments (CVE's) software also known as networked virtual environments (NVE's), and suggest how to improve the existing user interface by designing an alternative graphical user interface (GUI) for CVE's software. To reduce cost, most current and operative CVE's use the Internet and standard PC to create a visual virtual environment (VE), which can be shared by a large number of users. This project discusses CVE's and the importance of using a good GUI for a CVE system.